Gangrene of the toes in a patient with chronic myelogenous leukemia after long-term hydroxyurea therapy - Leo, Eugen; Krämer, Alwin; Hochhaus, Andreas; Krasniqi, Fatime; Hehlmann, Rüdiger; Ho, Anthony Dick (Annals of hematology, 2002)
Gangrene of the toes and digits appears to be a rare but very severe complication of long-term hydroxyurea therapy. Nothing is known regarding the pathophysiology and the type of vascular damage leading to this syndrome. Here we report a case of a 49-year-old male presenting with gangrene of the toes of both feet 4.5 years after initiation of hydroxyurea therapy for chronic myelogenous leukemia. Blisters on the toes occurred for the first time 9 months prior to hospitalization. Successively, all ten toes showed signs of beginning gangrene with one toe removed surgically 8 months before admission. Presence of diabetes mellitus or peripheral angiopathy was ruled out and platelet counts were within the physiologic range during the last years, excluding thrombocythemia as another rare cause for gangrene in patients with myeloproliferative diseases. Whereas perimalleolar ulcerations of the legs are a more common complication of hydroxyurea, gangrene of the toes as a consequence of hydroxyurea treatment has been described previously only once in the literature. At this point in time cessation of hydroxyurea treatment appears to be the only therapeutic option, thereby avoiding further progress of gangrene in patients with chronic myelogenous leukemia treated with hydroxyurea.